Hubungan antara Level Kedewasaan Manajemen Risiko, Kompleksitas Proyek, dan Kinerja Perusahaan ditinjau dari Perspektif Kontinjensi - , DEO FANI NUR WIJAYA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Project cannot be separated with risk. Risk management is one key success factors to achieve project goals and to improve the organization overall performance. Traditional theories in strategic management suggest that the higher the level of project risk management the better the organization performance. Such a theory was empirically supported by the empirical study that conducted in previous research. In the previous research the development of research instrument to measure the project risk management maturity level and the analysis with company performace had been carried out. On the other hand, more recent theories of strategic management suggest that there is no risk management that is applicable universally. It means that it is necessary to adjust project risk management for different characteristics of projects. Hence it is needed to conduct a further research to observe the phenomena from contingency perspective. The characteristic of the project can be reflected with project complexity. To provide a more robust model